2010
DOI: 10.1177/1046496410369563
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Knowledge Building in Teams: Can a New Team Training Strategy Help?

Abstract: Problem-solving teams composed of members possessing unique knowledge tend to be ineffective because of impediments that limit information sharing, including the sampling advantage of common information and differential schema structures among team members. Teams using a team training strategy aimed at ameliorating these impediments were expected to experience knowledge building and high performance. Data were collected from 40 teams of three co-located members, which were randomly assigned to a training or co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 38 publications
0
47
0
Order By: Relevance
“…Our main argument is that understanding team cognition as it occurs in real-world work settings requires an expanded view where cognition is seen as distributed and context dependent in a social environment in which artifacts often support cognitive functions ( Suchman, 1987 , 2007 ; Hutchins, 1995a ; Clancey, 1997 ; Hollnagel, 2002 ). Specifically, we advance the notion that artifacts support cognition by enabling the transition and development of internalized knowledge held by team members to externalized knowledge held at the team-level ( Fiore et al, 2010b ; Rentsch et al, 2010 , 2014 ). We draw from a diverse body of research and theory to emphasize that the functions of cognition can, and must be, viewed as sometimes occurring, not just “in” the head, but also “outside the head”; that is, viewing cognition in a broader context as distributed across the boundaries of brains, bodies, and environment ( Fiore, 2012 ; Cooke et al, 2013 ; Gorman, 2014 ).…”
Section: Cognition Technology and Teamsmentioning
confidence: 90%
See 1 more Smart Citation
“…Our main argument is that understanding team cognition as it occurs in real-world work settings requires an expanded view where cognition is seen as distributed and context dependent in a social environment in which artifacts often support cognitive functions ( Suchman, 1987 , 2007 ; Hutchins, 1995a ; Clancey, 1997 ; Hollnagel, 2002 ). Specifically, we advance the notion that artifacts support cognition by enabling the transition and development of internalized knowledge held by team members to externalized knowledge held at the team-level ( Fiore et al, 2010b ; Rentsch et al, 2010 , 2014 ). We draw from a diverse body of research and theory to emphasize that the functions of cognition can, and must be, viewed as sometimes occurring, not just “in” the head, but also “outside the head”; that is, viewing cognition in a broader context as distributed across the boundaries of brains, bodies, and environment ( Fiore, 2012 ; Cooke et al, 2013 ; Gorman, 2014 ).…”
Section: Cognition Technology and Teamsmentioning
confidence: 90%
“…While the aforementioned research looked at externalized cognition in support of teamwork in various complex work contexts, evidence for it also comes from research on training and learning. External representations in the form of “information boards” were used in a training study of knowledge building for a collaborative planning task ( Rentsch et al, 2010 ). Information boards supported the creation of artifacts in the form of posts and allowed team members to organize and visually manipulate these posts.…”
Section: Cognition Technology and Teamsmentioning
confidence: 99%
“…Use of knowledge tools seems to be beneficial not only because they structure the communication behaviors-such as speaking turns and sequence of topics that are discussed-but more particularly because they can provide team members with a cognitive structure that may help them to keep an overview of and efficiently remember the information that is presented in the team (Fiore, Cuevas, & Oser, 2003;Suthers & Hundhausen, 2003). This role of a shared graphical device as a cognitive structuring device gains support from an experimental study of Rentsch, Delise, Salas, and Letsky (2010), in which they trained half of their teams to exchange information on an information board using schema-enriched communication. They found that teams in the training condition made significantly more use of the information board and consequently had higher quality knowledge and more cognitive congruence than teams in a control condition.…”
Section: Knowledge Tools and Team Information Processingmentioning
confidence: 99%
“…Notwithstanding the evidence that poor coordination leads to poor performance and that coordinated teams achieve success, it is not entirely clear which sociocognitive mechanisms may help teams establish this knowledge coordination and likewise prevent poor coordination (Rentsch, Delise, Salas, & Letsky, 2010;Stasser & Titus, 1985). These research strands on team coordination insufficiently address the question of the underlying emergent states, processes, and activities contributing to coordination success (Ren & Argote, 2011).…”
Section: Team Coordinationmentioning
confidence: 99%